A YOLO Algorithm for Pattern Recognition in Images of Marine Species in Closed Seasons - (:unkn) unknown (Springer Nature Switzerland, 2024)
One of the main problems that arise in the process of extracting marine species during the closed seasons is the indiscriminate loading of marine species that are prohibited because they are in spawning season. These problems are often aggravated by the ...
Keywords: Reconocimiento de patrones; Especies marinas